Women’s Land Rights Conceptual Framework - CGIAR Research Program on Policies, Institutions, and Markets (2019)
The framework was used by the Women’s Land Rights Research Consortium to shape two rounds of grant-funded research papers. The first three studies, on Ethiopia, Uganda, and a comparative study of Indonesia, Peru, and Uganda have been completed.